Oral and topical administration of a geranyl acetophenone attenuates DNCB-induced atopic dermatitis-like skin lesions in BALB/c mice - Mohd Kasim, Vivi Nur Khalieda; Lee, Yu Zhao; Bakrin, Ikmal Hisyam; Hussain, Mohd Khairi; Israf, Daud Ahmad; Shaari, Khozirah; Tan, Ji Wei; Lee, Ming Tatt; Tham, Chau Ling (Nature Research, 2024)
Atopic dermatitis (AD) is a chronic, allergic inflammatory skin disorder that lacks a definite cure. Using a mouse DNCB-induced AD-like skin lesions model, this study evaluated the potential therapeutic utility of tHGA as an oral and topical treatment for AD. Male BALB/c mice were sensitised and challenged with 1% and 0.5% DNCB on their shaved dorsal skin. Mice in the treatment group were administered tHGA (20, 40, and 80 mg/kg) orally three times per week for 2 weeks, or tHGA (0.2%, 1%, and 5%) topically once daily for 12 days. On day 34, the mice were euthanized, and blood and dorsal skin samples were obtained for analysis. All doses of orally and topically administered tHGA significantly improved scratching, epidermal thickness, blood eosinophilia and mast cell infiltration. There was a minor discrepancy between the two routes of administration, with orally treated tHGA showing significant reductions in Scoring of Atopic Dermatitis (SCORAD), tissue eosinophil infiltration, serum IgE and skin IL-4 levels with treatment of 40 and 80 mg/kg tHGA, whereas topically applied tHGA showed significant reductions in all dosages. These findings suggest that tHGA exhibited therapeutic potential for AD as both oral and topical treatment ameliorates AD-like symptoms in the murine model. © The Author(s) 2024.